Repair of ascending aortic pseudoaneurysm eroding through the sternum. (January 2019) - Hasan, Sulaiman B; Khan, Fazal W; Hashmi, Shiraz; Tariq, Mohammad; Khan, Ghufranullah
In reoperation for an ascending aortic pseudoaneurysm eroding through the sternum, a left ventricular vent allows careful unhurried sternal division under deep hypothermic circulatory arrest. We repaired ascending aortic pseudoaneurysms in 2 patients who had undergone aortic valve implantation 6 and 21 months earlier. A minithoracotomy was made in the left 5th intercostal space, and a vent was placed in the left ventricular apex. Repair was accomplished with a bovine pericardial patch reinforced with a Teflon felt strip. Both patients made an uneventful recovery with good functional status at discharge at the 8- and 18-month follow-up.